Bruno Latour's Constructivism and Its Implications for the New Agency of Sociology - Robet, Robertus; R, U. Abdul Rozak (UI Scholars Hub, 2023)
Abstract Latour removes the boundaries between natural sciences and humanities. Science for Latour is cultural practise, at the same time in every cultural practice, nature and objects are also actively involved. In that sense, Latour's constructivism encourages the emergence of non-human actors as drivers of the societal changes. By that, he provoked sociology to expand its subject matter. The Social in sociology must be seen as an association involving human and non-human actors. Key words: Constructivism, Expansion of agency, actant, actor network theory.